2017
DOI: 10.1002/ddr.21393
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotensin NTS1 Receptor Agonist PD149163 Produces Antidepressant‐Like Effects in the Forced Swim Test: Further Support for Neurotensin as a Novel Pharmacologic Strategy for Antidepressant Drugs

Abstract: Preclinical Research Neurotensin is a nonbrain penetrant neuropeptide neurotransmitter that alters dopaminergic and serotonergic neurotransmission. Previous animal behavioral studies have demonstrated that intra-ventral tegmental administration of neurotensin and system administration of the selective neurotensin NTS receptor agonist, PD149163 produce antidepressant-like effects in a forced swim test and a differential reinforcement of low rate task, respectively. The present study sought to expand upon these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Elevated neurotensin levels were also observed in the Fawn-Hooded depression model (Mathé et al, 1998). On the other hand, neurotensin administration or treatment with NT1 agonists induce an antidepressant profile (Carey et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Elevated neurotensin levels were also observed in the Fawn-Hooded depression model (Mathé et al, 1998). On the other hand, neurotensin administration or treatment with NT1 agonists induce an antidepressant profile (Carey et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the caudal “tail” of the VTA that forms a continuum with the rostromedial tegmental nucleus (RMTg) is enriched with GABA-ergic neurons, which inhibit VTA DA neurons and serve as negative regulators of DA-mediated behaviors (Carr and Sesack, 2000; Margolis et al, 2012; Tan et al, 2012; van Zessen et al, 2012). Given that alterations in both VTA DA and Nts signaling have been implicated in the pathogenesis of drug addiction, depression, anxiety, schizophrenia, autism, pain processing and obesity, there is likely functional overlap of these systems (Boules et al, 2014; Caceda et al, 2012; Carey et al, 2017; Ellenbroek et al, 2016; Ferraro et al, 2016; Fitzpatrick et al, 2012; Howes et al, 2017; Kim and Mizuno, 2010; Li et al, 2016; Nestler and Carlezon Jr, 2006; Rothwell, 2016; Theoharides et al, 2016; Volkow et al, 2013). It is therefore critical to define the precise neural mechanisms by which Nts engages the VTA, to understand how it regulates such diverse physiology and how Nts signaling becomes maladaptive in disease.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported an increase in immobility behavior in NTSR1 KO mice [ 124 ]. Thereupon, NTSR1 agonist PD149163 significantly reduced time spent immobile in the forced swim test, exhibiting an antidepressant-like effect, similar to the antidepressant imipramine [ 125 ].…”
Section: The Neurotensinergic System In Stress and Stress-related Dis...mentioning
confidence: 99%